Neurostimulation in the treatment of primary headaches. Issue 5 (5th May 2016) - Miller, Sarah; Sinclair, Alex J; Davies, Brendan; Matharu, Manjit
Abstract : There is increasing interest in using neurostimulation to treat headache disorders. There are now several non-invasive and invasive stimulation devices available with some open-label series and small controlled trial studies that support their use. Non-invasive stimulation options include supraorbital stimulation (Cefaly), vagus nerve stimulation (gammaCore) and single-pulse transcranial magnetic stimulation (SpringTMS). Invasive procedures include occipital nerve stimulation, sphenopalatine ganglion stimulation and ventral tegmental area deep brain stimulation. These stimulation devices may find a place in the treatment pathway of headache disorders. Here, we explore the basic principles of neurostimulation for headache and overview the available methods of neurostimulation.